General synthesis of unnatural 4-, 5-, 6-, and 7-bromo-d-tryptophans by means of a regioselective indole alkylation. Issue 22 (28th May 2020) - Bartoccini, Francesca; Fanini, Fabiola; Retini, Michele; Piersanti, Giovanni
Graphical abstract: Highlights: General synthesis of enantiopure bromotryptophans. Regioselective C3-alkylation of (NH)-indoles. Serine-derived cyclic sulfamidate as a suitable source for the amino acid fragment. One-pot double-deprotection reaction with a single reagent. Abstract: A general two-step approach to enantiopure bromotryptophans from unprotected bromoindoles has been developed. Indole nucleophiles prepared with MeMgCl in the presence of CuCl reacted with cyclic sulfamidates derived from enantiopure d -serine to form 4-, 5-, 6-, or 7-bromo-d -tryptophan and some other halogenated tryptophans in moderate yields but with complete regioselectivity. The bromotryptophan derivatives were deprotected using mild conditions.